Development and validation of a novel customized medium for the marine microbial culture: Alteration of biomarkers of expired - Alam, Md Morshedul; Ahmed, Redwan; Amin, Md Ariful; Hossain, Mohammad Nazir (Bioresearch Communications, 2021)
Marine microbes are difficult to culture and hence it takes expensive measure to study. Mostly metagenomics are suggested for marine microbial characterization instead of culturing them in a suitable medium. In this study, a new approach has been developed to culture the marine microorganisms. We customized the LB agar and liquid medium by adjusting the pH and salt concentration at seawater level and then studied the microbial load, their growth rate by turbidity assay and also identified their morphology through gram staining. This study ensures the comfortable growth of marine microbes at the laboratory level, which would further help the marine biotechnologists and microbiologists to work smoothly with marine microbial samples. Bioresearch Commu. 7(2): 999-1003, 2021 (June)